Sustainable Community participation in heritage conservation plans: A systematic literature review comparing international frameworks with practices - Abdel-Fattah, Ghada Fathy; Gabr, Muhammad Ibrahem; Ezzeldin, Mohamed (Journal of engineering sciences and information technology, 2025)
This paper presents a systematic literature review on international frameworks for community participation in heritage conservation, focusing on the practical application of these frameworks in Hong Kong and Macao. The review examines the key elements of Arnstein’s Ladder of Participation and the ICOMOS Burra Charter, assessing their effectiveness in promoting community inclusivity, values-based management, and sustainability in heritage conservation. The findings indicate that the Burra Charter provides a clear, values-based framework for managing heritage sites, promoting cultural preservation through inclusive stakeholder engagement. In contrast, Arnstein's Ladder offers a community-driven approach, encouraging local involvement and empowerment but faces challenges in environments with limited regulatory flexibility. This paper highlights the diverse approaches to community engagement in heritage conservation, with Macao demonstrating a more inclusive, empowering model compared to Hong Kong’s consultative model. Based on these findings, this study provides strategic recommendations for improving community participation frameworks, contributing to more equitable, inclusive, and sustainable heritage conservation practices globally.
Keywords: Community participation; heritage conservation; Arnstein’s Ladder; ICOMOS Burra Charter; Hong Kong; Macao; values-based management; cultural preservation